A signal peptide derived from hsp60 binds HLA-E and interferes with CD94/NKG2A recognition. - Michaëlsson, J; Teixeira de Matos, C; Achour, A; Lanier, L; Kärre, K; Söderström, K (2002)
Human histocompatibility leukocyte antigen (HLA)-E is a nonclassical major histocompatibility complex (MHC) class I molecule which presents a restricted set of nonameric peptides, derived mainly from the signal sequence of other MHC class I molecules. It interacts with CD94/NKG2 receptors expressed on the surface of natural killer (NK) cells and T cell subsets. Here we demonstrate that HLA-E also presents a peptide derived from the leader sequence of human heat shock protein 60 (hsp60). This peptide gains access to HLA-E intracellularly, resulting in up-regulated HLA-E/hsp60 signal peptide cell-surface levels on stressed cells. Notably, HLA-E molecules in complex with the hsp60 signal peptide are no longer recognized by CD94/NKG2A inhibitory receptors. Thus, during cellular stress an increased proportion of HLA-E molecules may bind the nonprotective hsp60 signal peptide, leading to a reduced capacity to inhibit a major NK cell population. Such stress induced peptide interference would gradually uncouple CD94/NKG2A inhibitory recognition and provide a mechanism for NK cells to detect stressed cells in a peptide-dependent manner.